Impacts of urban microclimate on summertime sensible and latent energy demand for cooling in residential buildings of Hong Kong. (15th December 2019) - Shi, Luyang; Luo, Zhiwen; Matthews, Wendy; Wang, Zixuan; Li, Yuguo; Liu, Jing
Abstract: The urban heat island (UHI) and urban moisture island (UMI) effect can be significant in Hong Kong due to its high-density land utilization, and this can strongly affect building energy performance. While the UHI' energy impact has been rather intensively studied recently, the UMI effect on latent energy is still underexplored, especially for humid subtropical climate like Hong Kong. This study investigated the intensity of UHI and UMI in Hong Kong, and its impacts on the sensible and latent cooling demand of residential buildings in summer. Firstly, a ten-year weather dataset from 2004–2013 for the six stations selected based on the local climate zone (LCZ) scheme was analysed. The results show that the urban area of Hong Kong appears as both a heat and moisture island during summer nights but as cooling and dry islands during daytime, and the nocturnal UHI and UMI intensity vary significantly with different LCZs. Furthermore, the energy performance of a typical residential building in Hong Kong was simulated with measured weather data for the selected stations as an input. The urban building shows a higher sensible cooling demand, approximately twice that of the comparative rural one, and the latent cooling demand could be up to 96% higher. Both sensible and latent cooling energy demand decrease with increasing LCZ grades. Our study highlights that both UHI and UMI effect should be considered in the estimation of building energy in Hong Kong due to their significant impacts on the cooling energy demand. Highlights: The UHI and UMI effect among various LCZs in Hong Kong are compared. The nocturnal UHII and UMII during summer both decreases with the increasing LCZ grades. The impact of UMI effect on latent cooling demand is investigated in Hong Kong. The combination of UHI and UMI effect leads to an increase in electricity demand for urban residential buildings.